Creating a Volunteer ESL Program in Madrid: Action Research for Program Design and Service Learning - Anne McCabe; Therese Gleason; Tom Hare (Networks: An Online Journal for Teacher Research, 2002)
One of the challenges of accommodating North American students in study abroad programs is providing opportunities for volunteerism, a given in North American culture but not in Spain. Thus, Saint Louis University's Madrid campus began a program during the Fall semester 2001 in which fluent speakers of English volunteer to teach the English language to members of the Madrid community, who attend classes free of charge. We-Anne as faculty advisor, Therese as program coordinator, and Tom as the first volunteer teacher-had very little idea of how the program would unfold, since we did not know what kind of response it would initially receive, both from the community and from possible volunteers. This was the first time we offered a program like this, and we did not know of any other similar programs to turn to for suggestions. From the outset, we decided to incorporate action research as an investigative means of moving toward our desired goal, finding the optimal approach to fit the needs of both the community and the volunteer teachers. Preliminary results from data analysis corroborate our efforts. After discussing our results, we suggest that programs such as this one can be of great benefit for volunteer teachers who would like to explore their development, in terms of understanding classroom contexts and the wider cultural context of their host country.